The Impact of Social Media Technology Development on Minors - Syalomita Dealova Melody Katili; Deitje S Pongoh; Deswita Dealove Matu; Injilia Grachiella Rumantir; Divano BlessTindas; Cliff Hiskia Tumuwo (Jurnal Syntax Admiration, 2024)
The rapid development of social media technology has significantly influenced various aspects of society, particularly among minors. This research aims to explore the impact of social media technology on minors, focusing on both the positive and negative consequences. As minors increasingly engage with social media platforms, they experience changes in social behaviors, self-esteem, and mental health. The research identifies various effects, such as enhanced connectivity and access to information, alongside risks like cyberbullying, addiction, and exposure to inappropriate content. Through surveys and interviews, this study investigates the extent of social media’s influence on minors and offers recommendations for parents, educators, and policymakers to mitigate potential harm. The findings emphasize the need for balanced and responsible use of social media to foster healthy online interactions among minors.